ANALISIS KEMANDIRIAN FISKAL DI KABUPATEN JAYAPURA - Dwi Fitriani; Yundy Hafizrianda; Ida Ayu Purba Riani (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
This study aims to find out how much fiscal independence in Jayapura Regency is by looking at how the development of regional income and how the level of fiscal independence in Jayapura Regency. To see how much the level of fiscal independence in Jayapura regency, the author uses financial independence analysis. One of the most highlighted and most influential decentralization in the development of regional development is fiscal decentralization which is the most important part in the implementation of regional autonomy. Fiscal policy is basically a government instrument or instrument that plays an important role in the economic system, which is useful to encourage economic growth, expand the basis of economic activity in various sectors, and specifically expand employment to reduce unemployment Based on the analysis obtained the description of the Jayapura District Fiscal Independence Level in the level of achievement of targets from 2012 - 2016 the level of achievement has not been able to achieve the expected target such as regional revenues that have not been fully realized well and the level of independence of the region which is in the position of an instructive pattern because of several problems faced by the Jayapura Regency Government itself.